Reading Comprehension Course Through a Genre-Oriented Approach at a School in Colombia - Andrés Rodríguez Sánchez (Asociación Colombiana de Profesores de Ingles, 2017)
This paper reports on an action-research study aimed at identifying the problems and needs of a specific group of tenth graders at a school in Colombia in relation to their reading comprehension in English in order to design, partially implement, and evaluate a genre-oriented syllabus. Findings show that the explicit instruction of metacognitive strategies helped students become more efficient readers, as well as the fact that the exposure and analysis of genres developed a better comprehension of different kinds of texts, making these students aware of the structure and patterns of the texts they were reading as they approached them with reading strategies that were appropriate for each genre and stage.